GAMBARAN HISTOPATOLOGIK LIMPA TIKUS BETINA GALUR Sprague Dawley YANG DIBERI EKSTRAK ETANOL AKAR PASAK BUMI (Eurycoma longifolia Jack) DAN DIINDUKSI 7,12-DIMETILBENZ(a)ANTRASEN - Nurhaini, Rahmi; Rahmawati, Farida; -, Sunyoto (CERATA Jurnal Ilmu Farmasi, 2010)
Pasak bumi roots (Eurycoma longifolia Jack) is one of medicine herbs that using as medication to cancer. Cancer can branched out in human with unwell condition. Spleen is one of the organ that responsible to immunological body. The aim of this research to know the influence of giving extract ethanolic of pasak bumi’s roots to histological examination of female rats Sprague Dawley strain which induced by 7,12-dimetilbenz(a)antrasen.The research was using 18 female rats that devide into 6 group, with every group consist of 3 rats. Group I, II, III are called the treatment group, that given extract ethanolic of root E. longifolia Jack with dose 12,6 mg/ Kg BW; 25,2 mg/ Kg BW and 50,4 mg/ Kg BW every day during 7 weeks, group IV was administrated DMBA with dose 20 mg/ Kg BW for 10 times (twice a weeks during 5 weeks). Group V was called solvent control, given corn oil for 10 times, and group VI was called a healthty group that only given foot and water every day. In the end of research, all rats were killed and the spleen was removed and the spleen of rats taked to weighting then make to be histology preparates. The result of spleen weight was processed with SPSS program and the histology preparates was observed the illustration from every group. The result of the statistic analysis the weight of spleen showed no significant difference between one group with other. Histological examination of the spleen in each group shows that there is no specific pathology change in every rats whether in extract treatment group, sick control group, solvent control, and healthty group. The conclusion of this research is administration of extract ethanolic pasak bumi roots (E. longifolia Jack) and induction DMBA 20 mg/ Kg BW didn’t cause the spleen damage yet, so couldn’t carry on the effect from by histological examination of rats spleen. Keywords : Eurycoma longifolia Jack, spleen, 7,12-dimethilbez(a)antrazen